Salt resistance genes revealed by functional metagenomics from brines and moderate-salinity rhizosphere within a hypersaline environment - Mirete, Salvador; Mora-Ruiz, Merit R.; Lamprecht-Grandío, María; de Figueras, Carolina G.; Rosselló-Móra, Ramon; González-Pastor, José E. (Frontiers in Microbiology, 2015)
Hypersaline environments are considered one of the most extreme habitats on earth and microorganisms have developed diverse molecular mechanisms of adaptation to withstand these conditions. The present study was aimed at identifying novel genes involved in salt resistance from the microbial communities of brines and the rhizosphere from the Es Trenc saltern (Mallorca, Spain). The microbial diversity assessed by pyrosequencing of 16S rRNA gene libraries revealed the presence of communities that are typical in such environments. Metagenomic libraries from brine and rhizosphere samples, were transferred to the osmosensitive strain Escherichia coli MKH13, and screened for salt resistance. As a result, eleven genes that conferred salt resistance were identified, some encoding for well known proteins previously related to osmoadaptation as a glycerol and a proton pump, whereas others encoded for proteins not previously related to this function in microorganisms as DNA/RNA helicases, an endonuclease III (Nth) and hypothetical proteins of unknown function. Furthermore, four of the retrieved genes were cloned and expressed in Bacillus subtilis and they also exhibited salt resistance in this bacterium, broadening the spectrum of bacterial species where these genes can operate. This is the first report of salt resistance genes recovered from metagenomes of a hypersaline environment.